1991
DOI: 10.1002/jez.1402570111
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in fusibility in the colonial hydroid Hydractinia symbiolongicarpus

Abstract: Invertebrate fusion and rejection responses are typically assumed to be mutually exclusive and temporally stable states. We here describe a segregant class appearing in an F1 cross of the colonial hydroid, Hydractinia symbiolongicarpus, that displays an ontogenetic change in fusibility. Reproductively immature offspring fuse to parental strains and have been observed to remain continuously fused for up to 76 days. By contrast, reproductively mature offspring initially fused with parental strains, only to separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…obs.). Second, Shenk and Buss (1991) confirmed von Hauenschild's (1954) observation of a third class of intergenotypic interaction in H. symbiolongicarpus, transitory fusion, in which two colonies, either parents and their offspring or a pair of full sibs, initially fuse, and subsequently unilaterally or bilaterally reject each another. Most recently, Mokady and Buss (1996), based on a series of incrosses and backcrosses derived from a single mated pair (one member of which was highly inbred) argued that, as in the ascidian genus Botryllus, a single, highly polymorphic locus with multiple codominant alleles controls allorecognition in H. symbiolongicarpus…”
supporting
confidence: 65%
See 4 more Smart Citations
“…obs.). Second, Shenk and Buss (1991) confirmed von Hauenschild's (1954) observation of a third class of intergenotypic interaction in H. symbiolongicarpus, transitory fusion, in which two colonies, either parents and their offspring or a pair of full sibs, initially fuse, and subsequently unilaterally or bilaterally reject each another. Most recently, Mokady and Buss (1996), based on a series of incrosses and backcrosses derived from a single mated pair (one member of which was highly inbred) argued that, as in the ascidian genus Botryllus, a single, highly polymorphic locus with multiple codominant alleles controls allorecognition in H. symbiolongicarpus…”
supporting
confidence: 65%
“…Preliminary data from a number of studies (e.g., Teissier 1929;Crowell 1950;von Hauenschild 1954von Hauenschild , 1956MUller 1964;Ivker 1972) revealed that close relatives fused considerably more often than distantly related individuals, suggesting that allorecognition specificity had a genetic basis. Later studies (Yund et al 1987;Shenk and Buss 1991) confirmed these observations, and extended them in several fundamental ways. First, it is now clear that in natural populations, virtually all (i.e., >95%) allogeneic interactions produce an incompatibility response, involving the unilateral or bilateral deployment of hyperplastic stolons (Yund et al 1987;our unpubl.…”
mentioning
confidence: 67%
See 3 more Smart Citations